The Implementation of Supply Chain Management at “Sale Pisang” Businesses to Face MEA - Zakiyyah, Amalina Maryam; Rosyidah, Ulya Anisatur (Kontribusia : Research Dissemination for Community Development, 2019)
Home Industry “Sale pisang” Banyuwangi UD. Della Sale is one of the many UMKM producers of Banyuwangi souvenirs. The home industry faces several problems, namely (1) the shelf life of the fried “sale pisang” product is relatively short because of draining oil process is not maximal. (2) Product marketing is still limited. Maharani Community seeks to increase the income of its assisted people by cooperating with UD. Della Sale and acts as a distributor of “sale pisang” products. However, members of the Maharani Community do not have the knowledge and skills of financial management and marketing, so it makes difficult to develop. Therefore, this activity aims to improve the quality of production and increase the demand for “sale pisang” products through Supply Chan Management to face competition in the era of the ASEAN Economic Community (MEA). In this PKM activity, there are 3 (three) activities with the following objectives: The first activity aims to provide appropriate technology in the form of Spinner machines for draining oil to prevent changes in taste and quality of “sale pisang”. And the packaging machine is a vacuum sealer to make the product more durable and long lasting. The second activity is designing e-commerce websites and providing knowledge and assistance for product marketing. The third activity aims to provide knowledge about financial management by providing financial management materials with UMKM accounting standards.